Diploma Students’ Attitude and Problems towards Online English Learning Implemented at University of Bengkulu - Erlinda Rizal; Irma Diani; Safnil Arsyad (English Education Study Program Faculty of Teacher Training and Education, 2021)
The objectives of this research are to investigate the emotional, cognitive, and behavioral attitudes and problems of the Diploma student of Economic and Bussiness Faculty and Math and Science Faculty in Universitas Bengkulu toward online English learning. This research is quantitative. The sample of this research was 145 students of Diploma students of Economic and Bussiness Faculty and Math and Science Faculty in Universitas Bengkulu. The data were gathered by using a questionnaire and interview and were analyzed by using SPSS 21. The findings showed that Diploma students have a positive attitude toward English in all aspects, Behavior, Cognitive, and Emotional aspect. In the Behavior aspect, the highest score was that indicated they have a positive attitude was Diploma students are always on time when online English learning. In the Cognitive aspect, the highest score was that indicated they have a positive attitude was they can analyze content in online English learning. In the Emotional aspect, the highest score was that indicated they have a positive attitude was wished they could speak English fluently. The last, problem faced by students were they lack the signal to be able to study online. The process of teaching and learning English online requires students to have a signal, so, they could connect to the internet network and there are also some of the students who find it difficult to understand lessons when online learning. In conclusion, most of the students have a positive attitude in three aspects. But, the students have to pay attention to their signals during online learning.